2020
DOI: 10.1080/23311975.2020.1788874
|View full text |Cite
|
Sign up to set email alerts
|

Keep customers coming back: Enhancing value and satisfaction in a mobile shopping application context

Abstract: Mobile shopping applications have become a popular channel to reach the omnipresent consumer of today. However, the market space has become highly competitive and as a consequence, cultivating repurchase behavior has become pivotal to retain market share and boost sustainability. While the literature regarding initial purchase via a mobile shopping application is well developed, knowledge of how to foster repurchase behavior in this context is still scarce. In order to address the gap in extant literature, thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 88 publications
1
5
0
Order By: Relevance
“…It shows that customers prefer value of the product purchased over other factors when visiting shopping malls. The finding is consistent with that of prior studies (Anwer et al, 2020;Fernandes & Barfknecht, 2020;Yusof, et al, 2021;Peng & Chen, 2019). Since shopping malls gather many retailers at a location, it is easier for customers to compare the products and to choose the product the gives the highest value for their money.…”
Section: Data Analysis and Findingssupporting
confidence: 91%
See 1 more Smart Citation
“…It shows that customers prefer value of the product purchased over other factors when visiting shopping malls. The finding is consistent with that of prior studies (Anwer et al, 2020;Fernandes & Barfknecht, 2020;Yusof, et al, 2021;Peng & Chen, 2019). Since shopping malls gather many retailers at a location, it is easier for customers to compare the products and to choose the product the gives the highest value for their money.…”
Section: Data Analysis and Findingssupporting
confidence: 91%
“…Since shopping malls offer a variety of products with various price tag, customers have options to choose products that they prefer. Previous studies have proven that the product value will lead to customer satisfaction and subsequently will affect their purchase intention (Anwer et al, 2020;Fernandes & Barfknecht, 2020;Yusof et al, 2021;Peng, & Chen, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, App enjoyment in this study refers to the sensation of joy, entertainment or pleasure derived from the use of a mobile App. In fact, enjoyment reflects the hedonic (intrinsic) value of a product or service, where the utility stems from affective or feeling states that the product or service generates [31,32]. Consumers are more likely to purchase products/services depending on feelings of joy and pleasure, mainly in the case of hedonic products (e.g., a mobile game) [33].…”
Section: Research Model and Its Hypothesesmentioning
confidence: 99%
“…Mobile apps are useful in increasing consumer stickiness as being the platform between retailer and buyers to create real-time interaction (Hsu & Tang, 2019). Fernandes and Barfknecht (2020) called today's consumer omnipresent consumer for whom mobile shopping applications have become a popular channel. Thakur (2018) indicated that the distinction of mobile app is connected with being more user-friendly and the possibility to enable retailers to take full advantage of mobile operating systems.…”
Section: Introductionmentioning
confidence: 99%